La référence pronominale en français et en mandarin : une étude contrastive basée sur un corpus de traductions bidirectionnelles - Juan Sun; Qiang Zhang (Discours)
This paper aims at a quantitative investigation on pronominal references in two typologically and geo-culturally distinct languages: French and Mandarin Chinese. By conducting monolingual and inter-linguistic analyses based on a parallel corpus consisting of authentic texts translated from French into Mandarin or in the opposite direction, we demonstrated that apropos of the choice of referential expressions there is a wide divergence between these two languages. In accordance with our expectations, it seems that French has a predilection for the use of pronominal references, whereas Mandarin is characterized by a high frequency of nominal repetitions and in particular of ellipses. This difference is in general linked to the specific features of the pronominal system in each of the two languages and explains to a large extent the striking contrast between the translation tendencies from French to Mandarin and from Mandarin to French.